From sterilisation failure to a cornual pregnancy - Yee Kyaing, Yee; Awi, Idi
Introduction: Female sterilisation prevents pregnancy by occluding or disrupting tubal patency so that the ovum cannot reach the uterus. It is accepted as an effective method and practicing worldwide. Case Description: A 38 -year-old gravida 5 Parity 3+1 lady presented with amenorrhoea 2 months and pain in right iliac fossa for 3 days. She had two previous lower segment caesarean sections and bilateral tubal ligation was done during the last caesarean section 5 years ago. Her urine pregnancy was positive and ultrasound examination showed gestational sac with foetal cardiac activity and crown rump length corresponded to 8weeks of pregnancy. Cervical excitation pain was positive on vaginal examination. Laparotomy showed right cornual ectopic pregnancy and cornual wedge resection and bilateral tubal salpingectomy were done. Previous bilateral tubal ligation stumps were seen. Discussion: Bilateral tubal ligation has the advantage of immediate effective contraception, but there is a small but definite incidence of failure. Failure rate ranges from 0.2% to 1.3%. If a pregnancy results from a failed female sterilization, the possibility of an ectopic pregnancy is about 15% to 33%. Evidences showed the failure rate is highest when the procedure is performed during caesarean section and puerperium. Therefore, couples should be informed about chances of failure and medical attention should be taken if there is suspicious of pregnancy to avoid delayed diagnosis and management.